2015
DOI: 10.1097/aln.0000000000000828
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of Cathepsin G in the Development of Chronic Postsurgical Pain

Abstract: This study demonstrated that CTSG is a pronociceptive mediator in both animal model and human study. CTSG represents a new target for pain control and a potential marker to predict patients who are prone to develop chronic pain after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…Severe acute postoperative pain increases the risk of chronic postsurgical pain, and this may introduce bias. 7 However, our previous study showed that intraoperative nitrous oxide administration has no effect on early postoperative analgesia. 17 Finally, we did not adjust subgroup analyses for multiple testing, and this may increase type I error.…”
Section: Discussionmentioning
confidence: 93%
“…Severe acute postoperative pain increases the risk of chronic postsurgical pain, and this may introduce bias. 7 However, our previous study showed that intraoperative nitrous oxide administration has no effect on early postoperative analgesia. 17 Finally, we did not adjust subgroup analyses for multiple testing, and this may increase type I error.…”
Section: Discussionmentioning
confidence: 93%
“…To test this hypothesis, we first evaluated expression of sortilin in CFA-induced chronic inflammatory pain model. We previously reported significantly increased thermal hyperalgesia after intraplantar injection of CFA 22. Classical signs, including edema and erythema of the left hind paws, with CFA injection were observed within 1 h and throughout the entire experiment (Supplementary Figure S1).…”
Section: Resultsmentioning
confidence: 77%
“…Mpo has been shown by gene knockout to exacerbate secondary injury after SCI (Kubota et al, 2012). Ctsg is a pronociceptive mediator in the spinal cord (Liu et al, 2015), as is carbonic anhydrases (gene Car1 ) (Asiedu et al, 2010). Neutrophil elastase, which is released by activated neutrophils, is reported to be a key mediator of secondary pathogenesis in SCI (Semple et al, 2015).…”
Section: Discussionmentioning
confidence: 99%